Quantum chemistry - McQuarrie, Donald A (New Delhi : Viva Books, 2003)
Quantum Chemistry is a comprehensive book for undergraduate students of Chemical Engineering. The book comprises chapters on the wave equation, the Schrodinger equation, the harmonic oscillator, three-dimensional systems, approximate methods and molecular spectroscopy. In addition, the book consists of several diagrams, illustrations and chemical equations for the students to understand the concepts of quantum chemistry better. This book is essential for students preparing for various competitive examinations like GATE and IES.
Index 512-519p.; Reprint 2015.
Keywords: Approximate mathods; Molecular spectroscopy; Harmonic oscillator